1
$\begingroup$

The problem is

Find two linearly independent solutions of $2x^2y'' -xy' + (-4 x + 1)y = 0, \, x>0$ of the form $y_1 = x^{r_1}(1 + a_1 x + a_2 x^2 + a_3 x^3 + \cdots)$ and $y_2 = x^{r_2}(1 + b_1 x + b_2 x^2 + b_3 x^3 + \cdots)$.

What I have done is below:

2 x^2*D[y, {x, 2}] - x D[y, x] + (-4 x + 1) y == 0 /. y -> x^r*(Sum[C[n]*x^n, {n, 0, 5}])

The result mathematica gave is

(1 - 4 x) x^r (C[0] + x C[1] + x^2 C[2] + x^3 C[3] + x^4 C[4] + x^5 C[5]) == 0

from which I conclude that D[y,x]is excuted before the replacement. How can I make D[y,x] excute after the replacement?

$\endgroup$
1
  • $\begingroup$ With[{y=replacement},D[y,x]] $\endgroup$
    – Coolwater
    Apr 27, 2014 at 9:03

2 Answers 2

2
$\begingroup$

One method I like to use for this is the Hold/Release, like this (notice the use of D for derivative in the Hold stage.

  ClearAll[x, y, n];
  eq = 2 x^2  Hold[D[y[x], {x, 2}]] - x Hold[D[y[x], x]] + (-4 x + 1) y[x] == 0;
  Release[eq /. y[x] -> x^r*(Sum[C[n]*x^n, {n, 0, 5}])]

Mathematica graphics

$\endgroup$
2
$\begingroup$
  solns = y[x] /. First@DSolve[2 x^2*D[y[x], {x, 2}] - x D[y[x], x] + (-4 x + 1) y[x]== 0, y[x], x]
  y1[x_] = solns /. {C[1] -> 1, C[2] -> 0}
  y2[x_] = solns /. {C[1] -> 0, C[2] -> 1}
(*  E^(2 Sqrt[2] Sqrt[x]) Sqrt[x]  *)
(* -((E^(-2 Sqrt[2] Sqrt[x]) Sqrt[x])/(2 Sqrt[2]))  *)
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.